High intensity microsett-based cocoyam - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The new cocoyam or tannia (Xanthosoma sagittifolium Schott) is an important starchy staple in the humid tropics, especially various parts of West and Central Africa, where the daughter-corms or cormels are consumed. The young leaves are also...